Changes in glutathione peroxidase activities and glutathione system indices in rat liver and intestine in endogenous intoxication intiation under controlled selenium consumtion - Pekhovskaya, T.A; Slyshenkov, V.S; Gurinovich, V.A; Petushok, N.E; Shevalye, A.A; Zaitsev, V.A; Zubarevich, L.A; Moiseenok, A.G (MTT, 2005)
We studied the content and the ratio of the glutathione oxidized and reduced forms (GSSG, GSH, total G) as well as glutathione reductase and glutathione peroxidase activities (t-BOOH and H2O2 substrates) in the liver, duodenal, small and large intestines of albino rats (Wistar CRL:(WI) WUBR) consuming a low selenium diet supplemented with sodium selenite (SS) in drinking water or the organic preparation Sedimethyldipyrasolyl selenide (DPS) (both at a dose of 0,1 mikrog Se/ml water). The Se-consumption with feed was 0,14 ppm. Some animals were administered intraperitoneally with E. coli lipopolysaccharide (Sigma, L-2630) at a dose of 400 mikrog LPS/kg body weight to provoke endogenous intoxication (EI, endotoxemia). The development of hyperthermia was monitored by measuring colonic temperature, increasing blood plasma oxidative stress indices and their slackening in SS and DPS consumption. EI elevated the GSSG concentration and reduced the liver GSH/GSSG ratio, which was not found in the SS- and DPS - supplemented animals. Glutathione peroxidase activity turned out to be considerably increased in consuming Secontaining preparations, however, the greatest increase was after the SS administration. The EI development in the duodenal, small and large intestinal mucosa was accompanied by an identical decrease of GSH amount, the GSH/GSSG ratio and total G. The SS consumption elevated the GSH/GSSG ratio in all the intestinal regions and the total G in the large intestine as well as activated glutathione reductase in the small intestine. Both the Se-containing compounds stabilized the mucosal G system (probably, synthesis of G) in EI, which was pronounced in the large intestine. The results obtained indicate considerable variations in formation of Se-cysteine liver and intestinal stores in consumption of organic and inorganic selenium forms and enables to optimize the schemes for prevention and pathogenetic treatment of oxidative stress- induced pathologic processes in hepatology and gastroenterology.
Keywords: Ka; selenite; dimethyldipyrasolyl selenide; glutathione peroxidase; glutathione reductase; glutathione; intestinal mucosa